WORKSHOP: CREATE AN E-MODULE INTERACTIVE WITH EBOOK CREATOR APLICATION: PELATIHAN: MEMBUAT E-MODUL INTERAKTIF DENGAN APLIKASI EBOOK CREATOR - Tuti Marlina; Fitriani, Siti Lailatul (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
The Covid-19 pandemic has had a huge impact, such as many schools in the world being closed to stop the spread of Covid-19. The impact of the Covid-19 pandemic has made the government create an online learning program. Online or online learning is learning based on digital media technology in which learning materials are sent electronically or in the form of files to students remotely using the internet with computer media. According to the government, online learning is considered the most effective and efficient way to learn in the midst of the current pandemic. In online learning, of course, teachers need to master technology. Technology or e-learning is a distance learning method using technology and the internet as a means of delivering material outside of traditional face-to-face classes. There are many advantages of e-learning, including: effective and efficient, can be followed by many people, can manage their own time, and independent teaching for students. Video Based Learning or video-based learning is one method that has become a trend in e-learning for a decade. The benefits of Video Based Learning have captivated the world of education since its creation. Because the human brain is wired to track movement and is attracted to movement, videos can make things more interesting than just text. For this reason, training to make learning videos for teachers and prospective teachers is very important, considering that currently technology has become a trend and is very often used.